Mechano-chemical stability and water effect on gas selectivity in mixed-metal zeolitic imidazolate frameworks: a systematic investigation from van der Waals corrected density functional theory. Issue 3 (2nd January 2020) - Dang, Diem Thi-Xuan; Nguyen, Huong Thi-Diem; Thoai, Nam; Kuo, Jer-Lai; Nguyen, Nhung Tuyet Thi; Nguyen-Manh, Duc
Abstract : A series of Zn/Cu Zeolitic Imidazolate Frameworks (ZIFs) ZIF-202, -203, and -204 are systematically investigated by Density Functional Theory (DFT) with and without van der Waals (vdW) corrections. Abstract : A series of Zn/Cu Zeolitic Imidazolate Frameworks (ZIFs) ZIF-202, -203, and -204 are systematically investigated by Density Functional Theory (DFT) with and without van der Waals (vdW) corrections. The elastic constants for non-solvent structures indicate that ZIF-202 and -204 are mechanically stable while ZIF-203 is unstable, which arises from the stiffness along the x -axis under a uniaxial strain in the PBE-D3 method. By considering the presence of solvents in ZIF-203, a structural phase transformation from a monoclinic to a triclinic structure is found which could be explained by the Jahn–Teller distortion. From the chemical bonding point of view, it is found that vdW interactions and hybridization between d-orbitals (copper) and p-orbitals (imidazolate) are the main-driving forces in stabilizing ZIF-202 and -204, respectively. The electronic structure calculations predict the presence of two optical transitions in the visible region in agreement with the experimental observation for ZIF-204 both without and with water. The DFT simulations reveal that CO2 molecules prefer to locate near imidazolate and water in dry and hydrated ZIF-204, respectively. The analysis of Canonical Monte Carlo (GCMC) simulations reveals that Coulomb interaction between CO2 and H2 O molecules is mainly responsible for the enhanced CO2 uptake and selectivity under humid conditions compared to dry ones.